Modernity and culture : from the Mediterranean to the Indian Ocean - Fawaz, Leila Tarazi, 1944-; Bayly, C. A. (Christopher Alan); Ilbert, Robert (Columbia University Press, 2002)
Between the 1890s and 1920s, cities in the vast region stretching from the Mediterranean Sea to the Indian Ocean were experiencing political, social, economic, and cultural changes that had been set in motion at least since the early nineteenth century. As the age of pre-colonial empires gave way to colonial and national states, there was a sense that a particular liberalism of culture and economy had been irretrievably lost to a more intolerant age. Avoiding such dichotomies as East/West and modernity/tradition, this book provides a comparative analysis of contested versions of th.